2013
DOI: 10.1002/jmri.24443
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of liver function with T1 relaxation time index on Gd‐EOB‐DTPA‐enhanced MRI: Comparison with signal intensity‐based indices

Abstract: The T1 relaxation time index has the potential to serve as an MRI-based liver function test, and is most strongly correlated with ICG clearance among the Gd-EOB-DTPA MRI-based indices investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 24 publications
(44 reference statements)
2
37
0
Order By: Relevance
“…Two recent studies by Kamimura et al [21] and Ding et al [20] have assessed the utility of T1 relaxometry before and after gadoxetic acid administration for the assessment of liver cirrhosis and liver function using a 3D-DFA technique at a 3 T (n = 99 patients) and 1.5 T (n = 100 patients) system respectively showing that this technique has potential to serve as an MRI-based liver function test. Compared to these studies, our study provides in-vitro validation of T1 relaxation values and information on intra-patient variability of T1 values in the largest published series of patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Two recent studies by Kamimura et al [21] and Ding et al [20] have assessed the utility of T1 relaxometry before and after gadoxetic acid administration for the assessment of liver cirrhosis and liver function using a 3D-DFA technique at a 3 T (n = 99 patients) and 1.5 T (n = 100 patients) system respectively showing that this technique has potential to serve as an MRI-based liver function test. Compared to these studies, our study provides in-vitro validation of T1 relaxation values and information on intra-patient variability of T1 values in the largest published series of patients.…”
Section: Discussionmentioning
confidence: 98%
“…To date, few studies have examined the ability of gadoxetic acid T1 relaxometry for diagnosing liver fibrosis and for prediction of liver Magnetic Resonance Imaging 33 (2015) 1075-1082 function [18][19][20][21] showing good results for assessment of severity of liver cirrhosis with significant differences in T1 relaxation times of the liver after gadoxetic acid administration between patients with normal liver function and patients with Child-Pugh A, B, and C cirrhosis. These data showed that this technique might provide suitable parameters for detecting and characterizing severity of cirrhosis.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have shown the relationship between liver function and T 1 relaxation time. Kamimura et al showed that the reduction rate of the T 1 relaxation time of liver parenchyma could distinguish Child-Pugh A and B from normal liver better than the relative enhancement of the liver using SI [23]. In their study, the SI of paravertebral muscle and the spleen were used as the SI reference for liver parenchyma, but the scale and rescale slopes were not used.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have demonstrated changes in T 1 -based quantification in the presence of disease and correlations with model for end-stage liver disease (MELD) scores. 39,40 …”
Section: Approaches To Mr Haemodynamic Imaging In the Livermentioning
confidence: 99%